Exit, Voice or Loyalty? An Investigation into Mandated Portability of Front-Loaded Private Health Plans - Juan Pablo Atal; Hanming Fang; Martin Karlsson; Nicolas R. Ziebarth (Institute of Labor Economics (IZA), 2017)
We study theoretically and empirically how consumers in an individual private longterm health insurance market with front-loaded contracts respond to newly mandated portability requirements of their old-age provisions. To foster competition, effective 2009, the German legislature made the portability of standardized old-age provisions mandatory. Our theoretical model predicts that the portability reform will increase internal plan switching. However, under plausible assumptions, it will not increase external insurer switching. Moreover, the portability reform will enable unhealthier enrollees to reoptimize their plans. We find confirmatory evidence for the theoretical predictions using claims panel data from a big private insurer.
Keywords: G22; I11; I18; 330; individual private health insurance; portability; old-age provisions; health plan switching; switching costs; health policy reform; consumer bargaining; retention